The Role Of Expropriation Clauses In Protection And Promotion Of Foreign Investments In Renewable Energy: An Essential But Overlooked Legal Consideration - Ghaziani, Moosa Akefi; Ghaziani, Mohammad Akefi (Indonesia Law Review, 2022)
Today the world is tackling climate change. The global threat of energy poverty along with the growing need for energy has escalated this crisis. The promotion of renewable energy sources is widely known as the main solution to this challenge. Many International and regional agreements address various aspects of renewable energy development such as trade, transit, security, and investment. Since not all states have the financial and technological abilities to develop this sector, foreign investment is recognised as a crucial prerequisite for the global deployment of renewable energies. Various investment agreements are signed to facilitate and promote investments. These instruments contain a mixture of obligations that have direct or indirect effects. Expropriation provisions which are often crystallised in the form of ‘a duty not to expropriate’ are among these obligations. This article analytically describes the legal aspects of this criterion and proposes trends that can better protect the foreign investments inter alia in this sector; a factor without which the foreign investors are normally reluctant to invest. It is concluded that restricted police power, guarantees of transfer, and a full compensation standard that entails the payment of compound interest are the prominent legal features that can best perform this task.